Kajian konseptual tentang kesedaran berwakaf dalam kalangan kakitangan UiTM Cawangan Kedah / Azyyati Anuar ... [et al.] - Anuar, Azyyati; Hussin, Rohayati; Manshor, Nurul Mazrah; Kasim, Noor Hidayah; Sadek, Daing Maruak (Universiti Teknologi MARA, Kedah, 2021)
The Government of Malaysia has targeted Public Universities (UA) to generate their own income to cover part of the university's management expenses without being overly dependent on funds from the government. Accordingly, UiTM Kedah Branch (UiTMCK) would also like to take the initiative to utilize wakaf instruments by helping UiTM Shah Alam to raise funds for the Projek Wakaf Pembinaan Kompleks Arshad Ayub as a source of income generation. Moreover, to ensure the university staff and students will gain the benefits. Nevertheless, how far society, especially UiTMCK staff, have an awareness of the importance of wakaf. Therefore, this paper aims to propose a conceptual study to identify wakaf awareness among UiTMCK staff. Besides, to consider several factors in determining the level of awareness of wakaf among UiTMCK staff. This study will be conducted quantitatively by using questionnaires in collecting the data. The permanent staff of UiTMCK will be selected as respondents. The data obtained will be analyzed using SPSS version 25 for measuring frequency, descriptive, and correlation. Finally, the findings will assist UiTMCK staff in giving awareness of the importance of wakaf and motivation to remain conscious not only for the Projek Wakaf Pembinaan Kompleks Arshad Ayub, but also for any other wakaf project throughout Malaysia.